Interactive Educational Games: Boosting Numeracy Skills in 4-5 Year-Olds Through Multimedia - Ayu Riski Yuniria; Cucu Atikah; Luluk Asmawati (STAI Hubbulwathan Duri, 2025)
Developing numeracy skills in early childhood is crucial for cognitive growth. However, children aged 4-5 often struggle with number recognition, counting, and distinguishing numerical symbols. This study aims to develop interactive multimedia educational games to enhance numeracy skills in young learners. This research employed the Research and Development (RD) method using the ADDIE development model. A small-scale sample of five children with numeracy difficulties was involved. Observations at TPA Idola Bangsa Cilegon revealed that existing numeracy learning media were limited to conventional tools such as whiteboards, number cards, and books, highlighting the need for engaging digital alternatives. The developed multimedia game was validated by experts, with material experts rating it at 80% and media experts at 88%. The effectiveness of the game was assessed using the N-Gain Score, yielding a medium improvement category (0.65) in children’s numeracy skills. Additionally, children's responses to the game reached 91%, indicating strong engagement and acceptance. The findings suggest that interactive multimedia games provide a more effective and engaging alternative to traditional learning methods, addressing children's numeracy challenges. Interactive multimedia educational games are feasible, effective, and well-received by young learners. Future research should explore the long-term impact of these tools on children's cognitive development and adapt them for broader educational settings.